Measles outbreak investigation in Berhet District, North Shewa, Ethiopia - Shimelis, Yohannes; Asrat, Anemaw; Tadege, Tesfahun; Feleke, Sefineh Fenta (Frontiers in Public Health, 2024)
Introduction Measles, though usually self-limiting, can have severe consequences influenced by factors such as vaccination and nutrition, notably vitamin A deficiency and malnutrition. Despite progress, contextual changes and implementation issues have hampered efforts, resulting in increased outbreaks and cases of measles. This study seeks to pinpoint outbreak features, risk factors, and strategies for preventing and controlling measles. Methods A descriptive cross-sectional study and a 1:2 unmatched case-control study design were employed. All 101 suspected measles cases listed on the line-list were included in the descriptive research, with 60 measles patients and 120 controls included in the case-control investigation. Line-list data were cleaned and analyzed using a pivot table in Microsoft Excel 2016. Subsequently, the data were cleaned, entered into Epi Info 7.2, and exported to SPSS 26 for analysis. Results Twenty cases occurred per 10,000 individuals. Men accounted for 67.3% of cases, with ages ranging from 5 months to 45 years and mean and standard deviations of 9.6 and 7.6, respectively. Age group of 5–14 years comprised 57.4% of cases, followed by 1–4 years with 24.8%. Being unvaccinated against measles showed an adjusted odds ratio (AOR) of 12.06 (95% CI: 3.12–46.52). Travel history to regions with active cases had an AOR of 5.73 (95% CI: 1.78–18.38). Contact with a measles patient showed an AOR of 10.3 (95% CI: 3.48–30.5). Understanding the measles transmission mechanism had an AOR of 0.164 (95% CI: 0.049–0.55), and awareness of the disease's preventability had an AOR of 0.233 (95% CI: 0.67–0.811). All factors were independently associated with the illness. Conclusion This outbreak affected a broader age range with a high attack rate, mainly in the age group of 5–14-years. Over 35% of cases lacked measles vaccination, indicating low administrative vaccine coverage. Factors contributing to the outbreak include lack of measles vaccination, travel to areas with active disease, contact with cases, and insufficient knowledge of measles transmission and prevention strategies among mothers and caregivers.